Understanding Occupational Aspirations among Indian School Students: The Role of School Climate, Family Influence, and Value Orientation - Prajapati, Archana; Devi, Sita (Journal of Neonatal Surgery, 2025)
The present study delves into the multifaceted concept of Vyavsayik Akanksha (Occupational Aspiration), which plays a pivotal role in shaping an individual's career trajectory and personal development. With growing socio-economic challenges and rapid transformations in education and employment landscapes, understanding the nature, determinants, and implications of occupational aspirations among students, particularly at the middle and higher secondary levels, has become. crucial. This paper investigates how factors such as school environment, family background, social and emotional intelligence, and value systems influence the occupational aspirations of students. Special emphasis is placed on the role of educational institutions and the school climate in nurturing or hindering these aspirations. Additionally, the study explores the significance of personal traits like ambition, self-efficacy, and value orientation in developing occupational goals. The research employs a mixed-method approach, incorporating surveys and interviews to derive insights from a diverse sample of students. The findings underscore the importance of a supportive school environment. effective guidance, and socio-emotional learning in empowering students to make informed and realistic occupational choices. This paper aims to contribute to educational policy and practice by advocating for value-based education and personalized career guidance, especially in developing regions of India